Modern Medical Life Statistics: their Role and Impact on Human Life - Khalifa, Malak Khaled Najm; Ahmed Salem, Sajad Mohmmed; Salman, Alia Raad Mohsen; Abboud, Batool Habib Abbas; ati Ramadan, Muntadher ahmed (American Journal of Biodiversity, 2025)
The majority of population with scanty or no understanding of statistical views deems statistics and medicine as a daunting task, a matter to be more regarded in enhancing the welfare or health of people. Some of the human communities perceive statistics, which plays a critical role in medical field, as only a science of digits or figures. Owing to this, the crucial view of statistics is not followed in medical or clinical trials. Hence, it is onerous to know: (i) Why the statistical point of views must be connected in the realm of medical science, particularly in clinical trial; (ii) How statistics is put to use and has developed attention with medicine; and (iii) How medical researchers test their hypothetical views have to be known. In spite of the appearance of new techniques and technology, statistics is still in use to interpret a broad course of data arising from a variety of disciplines. In the expansion of medicine, biology as well as pharmacy, physicians, researchers and scientists make use of different statistical methods not only to maintain the interpretability of warnings of traditional statistical tests; it nevertheless allows it to extend their conclusions beyond what is specific in the raw data . While medicine must continuously advance with the quit discoveries of science and technology, statistical methodologies used in medicine have to be unified with the medical or biological content and the ethical or societal desiderata. It is with all three intention of presenting statistical researches and findings with a view of enlightening this unfailing interplay. Later on, it is planned to guide doctors and biostaticians who are going to possess clinical trials. In general practice, the broader role of statistics is referred to in education, training and research of medical, biological and pharmaceutical scientists. It is with the above in mind that this humble venture has been made to encourage a broader view of Statistics in those working in medical field and to introduce a selection of the many statistical issues presently in focus in this realm.